Analisis Semiotik Pesan Dakwah Lirik Lagu Nasyid “Pandangan Mata” Karya Hijjaz (Model Charles Sanders Peirce) - Ridho, Ali (el Buhuth: Borneo Journal of Islamic Studies, 2019)
The road to preaching has a variety of ways, especially the media used. Among them is through the type of Nasyid religious music media. Among the Nasyid groups whose songs contain calls for Islamic da'wah are the Nasyid Hijjaz Group with the song "Mata Mata". From the observations of the author in it the message of the values of da'wah is stored, that believing Muslims are subject to the obligation to always improve the condition of their heart. The Eye View song, illustrates that a Muslim is required to improve the condition of the heart by purifying him from the filth of immorality that leads to the valley of sin. Giving birth to humiliation and addiction, the sins of the heart that make the heart become rusty. If sin through immorality continues to grow, then rust will dominate until it becomes the closing. While leaving immorality is life for the heart. Sin also diverts the heart from its health and straightness to pain and abuse. He will continue to be sick, unable to benefit from the parts that support his life and piety. The heart is the captain of the faithful servant who is the main foundation of the assessment of the good or bad of a servant before Allah SWT. a clean heart (qalb salim) will be able to deliver its owner to happiness in the world and the hereafter.